Specific inhalation challenge with flour induced release of brain‐derived neurotrophic factor in nasal fluid. Issue 1 (17th September 2013) - Castano, Roberto; Welman, Melanie; Trudeau, Carole; Castellanos, Lucero; Maghni, Karim; Malo, Jean‐Luc
<x xml:space="preserve">Abstract</x> Background Neurotrophins may play a role in the pathophysiology of allergic occupational rhinitis (OR). We sought to investigate whether an immediate allergic reaction that induces nasal inflammation is also able to induce changes in levels of brain‐derived neurotrophic factor (BDNF) in nasal lavage (NAL) fluid from patients with allergic OR. Methods Ten patients sensitized to flour underwent control and active specific inhalation challenge (SIC) on consecutive days. Nasal response to SIC was monitored with acoustic rhinometry and symptoms recording. NAL was performed before and 30 minutes, 6 hours, and 24 hours after control and active challenge for the assessment of levels of BDNF and inflammatory cells in NAL fluid. Results In contrast to control day, flour challenge induced immediate clinical reactions in all subjects. After flour challenge, a significant increase in levels of BDNF in NAL fluid was observed at 6 hours after challenge (p < 0.05). Also, a significant increase in the number of eosinophils in NAL fluid at 30 minutes (p < 0.01), 6 hours (p < 0.01), and 24 hours (p = 0.05) postchallenge was observed. Also, levels of BDNF in NAL fluid were significantly higher at 30 minutes after flour challenge (p = 0.02) in comparison to levels on the control day at the same postchallenge time. A marginally significant positive correlation between BDNF levels and eosinophil counts at 30 minutes (r = 0.60, p = 0.06) and at 6 hours (r = 0.50, p = 0.08) after flour challenge was noted. Conclusion We showed that BDNF is released in nasal fluid after SIC with flour. Results support the suggestion that neurotrophins may play a role in the pathogenesis of allergic OR.